Women with Type 1 Diabetes Mellitus: Effect of Disease and Psychosocial-Related Correlates on Health-Related Quality of Life - Syed Wasif Gillani; Irfan Altaf Ansari; Hisham A. Zaghloul; Mohi Iqbal Mohammad Abdul; Syed Azhar Syed Sulaiman; Mirza R. Baig; Hassaan Anwar Rathore (Journal of Diabetes Research)
Background. This study is aimed at investigating the various disease-specific and health-related psychosocial concepts of HRQOL among insulin-dependent diabetes mellitus (IDDM) and understanding the gender differences in HRQOL among IDDM patients. Methods. A cross-sectional observational study was conducted to assess the effect of health-related and psychosocial correlates on HRQOL of IDDM patients in Penang, Malaysia. The participants were recruited from five governmental diabetic clinics. Patients with insulin use only, IDDM diagnosed at least 1 year earlier, were identified from clinical registers. The sample was then age stratified for 20–64 years, and severe complications (e.g., end-stage renal failure, hemodialysis, and liver cirrhosis) were excluded; a total of 1003 participants were enrolled in the study. Multivariate regression analysis was used to predict the response. Results. A total of 853 (100%) participants were enrolled and completed the study. Women exhibited significantly higher/better mental health (p<0.013) and health perception scores (p<0.001) despite high prevalence of impaired role (49.2%), social (24.2%), and physical (40.5%) functionings as compared to men. Women with longer diabetes exposure and uncontrolled glycemic levels (HbA1c) have poorer HRQOL. Availability of social support showed no significant association with either HRQOL or diabetes distress levels. Diabetes distress levels remained not associated with social support. Women also showed significantly higher association with health perception (15% versus 13% men, p<0.001) and mental health (13% versus 11% men, p<0.001) in diabetes-specific psychosocial factors. Thus, among women alone, diabetes-related specific and psychosocial factors explained 15% and 13% of variations in HRQOL extents, respectively. Conclusion. Women exhibit extensive and significant patterns with health-related factors and diabetes-specific psychosocial factors (self-efficacy, social support, and DLC) to improve HRQOL. Also, women have significantly high reported distress levels and low social functioning compared to men.